2022
DOI: 10.1038/s41398-022-02229-w
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic model development for schizophrenia based on peripheral blood mononuclear cell subtype-specific expression of metabolic markers

Abstract: A significant proportion of the personal and economic burden of schizophrenia can be attributed to the late diagnosis or misdiagnosis of the disorder. A novel, objective diagnostic approaches could facilitate the early detection and treatment of schizophrenia and improve patient outcomes. In the present study, we aimed to identify robust schizophrenia-specific blood biomarkers, with the goal of developing an accurate diagnostic model. The levels of selected serum and peripheral blood mononuclear cell (PBMC) ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…PBMC is a widely used model to study person-specific cell dynamics and is increasingly used as a source of biomarkers for diagnostics and prediction [ 35 37 ]. The crude microsomal fractions derived from the individual PBMC contain metabolic enzymes like CYPs that are involved in the turnover of drugs or endogenous substrates such as retinoids and are thus often used to study metabolic pathways.…”
Section: Methodsmentioning
confidence: 99%
“…PBMC is a widely used model to study person-specific cell dynamics and is increasingly used as a source of biomarkers for diagnostics and prediction [ 35 37 ]. The crude microsomal fractions derived from the individual PBMC contain metabolic enzymes like CYPs that are involved in the turnover of drugs or endogenous substrates such as retinoids and are thus often used to study metabolic pathways.…”
Section: Methodsmentioning
confidence: 99%
“…Of potential clinical utility is the presence of various monocyte-specific markers for treatment response monitoring and differential diagnosis of SCZ. Specifically, reduced glucose transporter (GLUT1) expression in monocytes has been proposed as a key diagnostic feature to distinguish SCZ from BD, MDD, and autistic spectrum disorder [ 89 ], while soluble CD14, an identity marker of circulating monocytes, could accurately predict subsequent SCZ diagnosis [ 90 ]. A monocytic transcription signature was also proposed as a candidate marker for monitoring beneficial simvastatin response in patients with SCZ [ 91 ].…”
Section: Alterations In Circulating Immune Cells In Sczmentioning
confidence: 99%
“…Monocytes Increased total monocyte counts [62][63][64] Increased classical monocyte counts [66] Increased pro-inflammatory monocyte counts [67] Increased monocyte to lymphocyte ratio [68] Increased monocyte to HDL ratio [72,73] Increased TREM1/2 [79,80] Increased ATF3/EGR3 [78] Increased HLA-DR [82] Increased phagocytosis [81] Increased IL-1, IL-6, TNF-α [83,85,86] Increased CD36 [93] Increased reactive oxygen species [92] Alterations in TLR4 signaling [84,87,88] Unique interferon gene signature [77] Reduced GLUT1 [89] Granulocytes Increased neutrophil counts [68,94-99] Increased neutrophil to lymphocyte ratio [100,101] Increased oxidative stress [108] Increased malonaldehyde [122] Increased superoxide anion [123,123] Increased phagocytosis [81,124] Natural killer cells Increased total counts [68] Decreased total counts [125][126][127] No change in total counts [128] Increased cytotoxicity [132] Decreased cytotoxicity [129,130] No change in cytotoxicity [121] Increased NKG2C [133] Increased S100B [134] Table 1. Cont.…”
Section: Peripheral Blood Featuresmentioning
confidence: 99%
“…In addition, the absence of a specific molecular basis for diagnosis in psychiatry at this time prevents the creation of diagnostic tools, and diagnosis in MDD is still reliant on symptomatology. In recent years, peripheral tissues, such as blood, are gradually being used to study psychiatric illnesses [15][16][17][18], and some molecular mediators found in these studies may be used as possible biomarkers [19][20][21][22]. Thus, serum investigations are necessary to understand how they function in MDD and if they have potential as candidate biomarkers for the diagnosis of MDD.…”
Section: Introductionmentioning
confidence: 99%